POWER RELATIONS IN THE NEUTRALITY OF VILLAGE HEADS DURING REGIONAL HEAD ELECTIONS IN MAROS REGENCY - Andi Muh. Fadhal Hiqh T. Pangera; jumadi; Bakhtiar; Hasruddin Nur (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to: (1) analyze the neutrality of village heads in the implementation of the Regional Head Election (Pilkada) in Maros Regency; (2) analyze the factors influencing the non-neutrality of village heads during the Pilkada in Maros Regency; and (3) identify the forms of non-neutrality practiced by village heads during the Pilkada in Maros Regency. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The informants consisted of 17 participants, including representatives from the Regency Election Supervisory Agency (Bawaslu), villagelevel election supervisors, community leaders, youth leaders, and teachers. Data analysis was conducted through three stages: data condensation, data display, and conclusion drawing. The results of the study indicate that: (1) regarding the neutrality of village heads in the implementation of the Pilkada in Maros Regency, there were two forms of non-neutral behavior committed by village heads during the 2024 Pilkada process. Furthermore, public knowledge regarding village head neutrality was generally adequate, although some community members still lacked understanding of the concept. In terms of regulations, village heads were aware of and understood the legal provisions concerning neutrality, although some failed to remain neutral in practice. Likewise, most community members were familiar with the regulations governing village head neutrality, while a small number remained unaware. (2) The factors influencing the non-neutrality of village heads consisted of: (a) external political pressure and influence; (b) village aspirations and interests; and (c) legal awareness and political culture.